THE EFFICIENCY OF SACCAHROMYCES CEREVISIAE STRAIN ISOLATED FROM PALM WINE IN THE PRODUCTION OF BURUKUTU - Danmadami; Yabaya; O, Yahaya; Abraham; M, Bobai; A.A, Orukotan (International Journal of Research -GRANTHAALAYAH, 2017)
Non-availability and relatively high cost of obtaining the most effective commercially alcoholic fermentative Saccharomyces cereviciae strain is a major constrain in development and sustaining local industrial fermentation process. This study determined the alcoholic fermentative efficiency of Saccharomyces cereviciae strains isolated from palm wine in the production of burukutu. Palm wine was collected from Kachia, a sub-urban area of Kaduna, Kaduna State, Nigeria. Isolation was carried out using Sabouroud dextrose agar. Identification and characterization of Saccharomyces cereviciae from palm wine was carried out by microscopy and conventional biochemical methods and Analytical Profile Index. Alcoholic fermentative efficiency of the yeasts isolates was determined through fermentation of sorghum for the production of Burukutu. Ethanol tolerance and some physiological test were conducted. Cultural and morphological characteristics revealed smooth, creamy and white colonies on SDA, while cellular morphology was round and budded in arrangement. Biochemical identification and API showed isolate that was Glucose, Galactose, Raffinose, Acetyl D glucosamine positive and Glycerol, Inositol, Sorbitol, Arabinose, D –xylose, Adonitol Xylitol, Celiobiose, 2 – Ketoglutanal, Lactose, Maltose, Tretialose, Melezitose negative. HyphoePsedudohyphae and the control carbohydrate utilized were negative. The ethanol tolerance characteristics of the yeast revealed that the isolate had 8% ethanol tolerant. The pH of the Burukutu produced with Saccharomyces cerevisiae isolated from palm wine ranged from 3.8 – 6.2, in a manner showing pH decrease from 6.2 to 3.8 Within 24 hours’ fermentation period. Volatile acidity was also observed to have reduced during the study period. The total viable yeast also increased gradually, thus showing its ability to to metabolize sugar in sorghum to produce alcohol in burukutu.